2021
DOI: 10.1002/ece3.7169
|View full text |Cite
|
Sign up to set email alerts
|

Habitat filtering drives the local distribution of congeneric species in a Brazilian white‐sand flooded tropical forest

Abstract: The investigation of ecological processes that maintain species coexistence is revealing in naturally disturbed environments such as the white‐sand tropical forest, which is subject to periodic flooding that might pose strong habitat filtering to tree species. Congeneric species are a good model to investigate the relative importance of ecological processes that maintain high species diversity because they tend to exploit the same limiting resources and/or have similar tolerance limits to the same environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 91 publications
(124 reference statements)
0
9
0
Order By: Relevance
“…Closely related congeneric species tend to share many similar phenotypic traits and ecological traits and utilize shared resources in similar ways, making it impossible for them to un‐coexist stably (Mooney et al, 2008 ; Ribeiro et al, 2021a ; Simberloff, 1970 ). Previous studies have shown strong negative associations between congeneric species with similar ecological properties (Wang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Closely related congeneric species tend to share many similar phenotypic traits and ecological traits and utilize shared resources in similar ways, making it impossible for them to un‐coexist stably (Mooney et al, 2008 ; Ribeiro et al, 2021a ; Simberloff, 1970 ). Previous studies have shown strong negative associations between congeneric species with similar ecological properties (Wang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that habitat specialization may support the coexistence of congeneric species in sympatry (Allié et al, 2015 ; Itoh et al, 2010 ; Yamasaki et al, 2013 ). Ribeiro et al ( 2021 ) found that three congeneric species were spatially independent and exhibited similar habitat preferences in Brazilian white‐sand flooded tropical forests. Our hypotheses need to be further evaluated under the context of environmental influence on the spatial distribution of species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial patterns may conserve an imprint of past processes, and therefore constitute an ecological archive from which we may recover information about the underlying processes (Wiegand et al, 2003(Wiegand et al, , 2009Grimm et al, 2005;McIntire and Fajardo, 2009;Perea et al, 2021). Indeed, spatial patterns of tree species have provided valuable information to obtain insights on intra and inter-specific interactions as well as forest community structure (Stoll and Bergius, 2005;Wiegand et al, 2012), and spatial pattern analysis is a focus of current forest ecological research (Wiegand and Moloney, 2014;Velázquez et al, 2016;Ben-Said, 2021;Nguyen et al, 2021;Perea et al, 2021;Ribeiro et al, 2021;Wiegand et al, 2021). Techniques of spatial point pattern analysis have also been used to detect spatial association patterns and signatures of habitat association, facilitation and competition in TDFs (e.g., Espinosa et al, 2016;Álvarez-Yépiz et al, 2017;Gusmán-M et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studying spatial association between trees at both intra-and interspecific levels is important to reveal the existence of interactions and their types (Jia et al 2016). SPPA has been mostly carried out for woody species compared to herbaceous plants (but see Riginos et al 2005;De Luis et al 2008;Raventós et al 2010) and various mechanisms controlling species spatial patterns are currently investigated in temperate (Getzin et al 2006;Hao et al 2007;Wang et al 2010a;Zhang et al 2010Zhang et al , 2013Martínez et al 2013;Liu et al 2014;Yao et al 2016;Carrer et al 2018;Wang et al 2018;Szmyt and Tarasiuk 2018;Zhang et al 2020), tropical (Wiegand et al 2007a;Lan et al 2012;Miao et al 2018;Nguyen et al 2016;Cordero et al 2016;Ribeiro et al 2021, Nguyen et al 2018a and Mediterranean regions (Camarero et al 2005;De Luis et al 2008;Lingua et al 2008;Comas et al 2009;Raventós et al 2010;Garcia-Cervigon et al 2017;Abellanas and Pérez-Moreno 2018;Ben-Said et al 2020). Assuming the crucial role of biotic processes to be a driver of species spatial pattern, various environmental factors can be involved in structuring plant communities including water availability (Zheng et al 2017), soil nutrients (Riginos et al 2005;Zhao et al 2015), moisture (Fajardo et al 2006;…”
Section: Introductionmentioning
confidence: 99%